1998
DOI: 10.1002/(sici)1097-4644(19980801)70:2<281::aid-jcb13>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma protein tethered to promoter DNA represses TBP-mediated transcription

Abstract: The retinoblastoma (RB) tumour suppressor protein negatively regulates cell proliferation by modulating transcription of growth-regulatory genes. Recruitment of Rb to promoters, by association with E2F complex or by fusion with heterologous DNA-binding domains, demonstrated that Rb represses directly transcription. Recent studies also suggest that the RB protein is able to repress gene transcription mediated by the RNA polymerase I and III. Since the TATA-binding protein (TBP) is an important component for tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Recent data indicate that the Rb-associated histone deacetylase complex is involved in transcriptional repression of E2F responsive genes (29,30,31,32,(33)(34)(35). Our results (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Recent data indicate that the Rb-associated histone deacetylase complex is involved in transcriptional repression of E2F responsive genes (29,30,31,32,(33)(34)(35). Our results (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Sp3 is a ubiquitously expressed transcription factor, closely related to Sp1 but, unlike Sp1, often functioning as a transcriptional repressor by means of interacting with GC-rich Sp1-like sites (31,32). It has also been shown that Sp3 acts as a bi-functional regulator whose activating or repressing activity is dependent upon both the promoter and the cellular context (27,33).…”
Section: Our Results Show That Tieg2 Was An Activator For the Human Mmentioning
confidence: 99%
“…The involvement of the DRE–DREF system in TBP gene expression suggests that the expression of TBP is also related to cell division and cell proliferation. In addition, TBP is known to be a major target for the regulation of the expression of genes related to cell proliferation, because of its interaction with transcription factors such as retinoblastoma (RB) protein [30], p53 [31,32], E1A [33], c‐Myc [34], and v‐Myb [35]. For these reasons we believe that the regulation of TBP gene expression is likely to be important for cell division and/or proliferation.…”
Section: Discussionmentioning
confidence: 99%